2019
DOI: 10.5296/ijafr.v9i1.14243
|View full text |Cite
|
Sign up to set email alerts
|

On The Dynamic Dependence Between Oil Prices and Stock Market Returns: A Copula-GARCH Approach

Abstract: This article investigates the conditional dependence structure between crude oil price and stock returns markets. Our empirical analysis relies on an asset pricing model that accommodates the asset return dependence through the copula functions. The obtained results indicate the superiority of our approach and show evidence of significant tail dependence of the returns in unstable financial environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The study showed a correlation between the financial and real estate markets in mainland China and Hong Kong (Sui et al, 2019); and some scholars based on the model and the empirical analysis of the Istanbul Stock Exchange, analyze the correlation between oil price and the stock market. The results show that all stock market returns and oil price changes are positively correlated, and there is a weak dependence structure between Istanbul Stock Exchange and Brent crude oil price (Ayse 2019;Kouki et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…The study showed a correlation between the financial and real estate markets in mainland China and Hong Kong (Sui et al, 2019); and some scholars based on the model and the empirical analysis of the Istanbul Stock Exchange, analyze the correlation between oil price and the stock market. The results show that all stock market returns and oil price changes are positively correlated, and there is a weak dependence structure between Istanbul Stock Exchange and Brent crude oil price (Ayse 2019;Kouki et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…The study showed a correlation between the financial and real estate markets in mainland China and Hong Kong (Sui et al, 2019); and some scholars based on the model and the empirical analysis of the Istanbul Stock Exchange, analyze the correlation between oil price and the stock market. The results show that all stock market returns and oil price changes are positively correlated, and there is a weak dependence structure between Istanbul Stock Exchange and Brent crude oil price (Ayse 2019;Kouki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%